Subclavian Steal Syndrome Treated by Endovascular Approach in the Interventional Neurology Clinic - Vedat Ali Yürekli; Süleyman Kutluhan; Erdem Gürkaş; Gürdal Orhan (Türk Nöroloji Dergisi, 2013)
Subclavian steal syndrome is a clinical feature displayed due to decrease or reverse of blood flow in the ipsilateral vertebral artery resulting from severe stenosis or occlusion of the proximal subclavian artery. Subclavian steal syndrome was first described and defined by angiography. The best treatment of subclavian steal syndrome is still controversial, although balloon angioplasty and/or stenting procedures have been generally accepted during the past decade. We report a case of subclavian steal syndrome successfully treated by stenting of the left subclavian artery in our interventional neurology clinic